AL-SHIGHAH WA AL-QADHIYYAH FI AL-QISSHAH AL-QASHIRAH ATHFAALU AL-GHAABAH LI MUHAMMAD ‘ATHIYAH AL-ABRASY - Mustofa, Arif; Fathurrahman, Andi Muhammad; Surur, Misbahus (Annual International Conferences on Language, Literature, and Media, 2023)
Case grammar is a modification of the meaning of transformation grammar which reintroduces the conceptual framework of case relations from traditional grammar, but maintains and maintains a distinction between the inner structure and the surface structure of generative grammar provided that the word "in". This study aims to reveal the formula and describe the assumptions in the short story Athfaalu Al-Ghaabah by Muhammad Attia Al-Abrashi from the linguistic perspective of case grammar Charles J. Fillmore, using the qualitative approach to the research, concludes from this study several points, which are the tense form (past, present, future), the aspect form (past, state, future), the negative form (no, why, will not), the adverbial form (again, more beautiful), the formula is moody (no doubt). In terms of the case, there are nine positions, which are the case of the subject (I am), the case of the predicate (I will give), the case of the instrument (an eye), the case of the object (I asked for it), the case of the source (the gazelle, the rain), the case of the object (the city, the house, the palace) and the case of the place (in the city, the enchanted garden) the state of time (four years).